The study of fatty-acid spectrum of blood serum in patients with aspirin associated polypous rhinosinusitis - Кошель, Іванна Василівна (ScienceRise: Medical Science, 2016)
Aim of research – to study the composition of the main representatives of polyunsaturated and saturated fatty acids in blood serum of patients with chronic polypous rhinosinusitis, associated with intolerance to acetylsalicinic acid. Materials and methods. The fatty-acid composition of blood serum was determined by the method of capillary gas-liquid chromatography in 20 ill and 7 healthy donors. Results: The change of composition of unsaturated fatty acids is in increase of arachidonic acid level, decrease of the content of its main predecessors – linoleic and eicosapentaenoic acids, normal level of intermediate products:α – and γ – linoleic acid and increase of the level of oleic acid. The content of the main saturated fatty acids: palmitic, stearic, arachidic ones is increased. The fatty acids imbalance testifies to the proinflammatory directionality of lipid metabolism. Conclusions: 1. The increase of the level of polyunsaturated (arachdonic and oleic acids) leads to the compensatory decrease of the level of the main predecessors of arachinonic – linoleic and eicosapentaenoic acids. This mechanism allows keep the intermediate products of synthesis of arachidonic acid - α – and γ – linoleic acids at the normal level. 2. The content of saturated fatty acids with alternative biological effects is increased in blood serum as a compensatory mechanism of leveling of biological effects of polyunsaturated fatty acids and their metabolites,. 3. The revealed imbalance of fatty acids testifies to the proinflammatory directionality of the lipid metabolism. 4. The changes of fatty-acid spectrum of lipids in the blood serum prove the hypothesis of “genetic block COG1” as the main pathogenetic link of aspirin associated polypous rhinosinusitis